Overcoming Student’s Misconception through Implementation of Metacognitive Skills-Based Instructional Materials in Energetics - Nasrudin, H.; Azizah, U. (Jurnal Pendidikan IPA Indonesia, 2020)
Developing metacognitive skills is a prominent objective in the education field. Several institutions use the skills to facilitate studentsÃ¢â‚¬â„¢ thinking processes. This study aims to overcome student misconceptions in energetic materials by implementing teaching materials based on metacognitive skills. Several studies have shown that metacognitive skills have played a role in reducing misconceptions through the process of problem-solving in science learning. The subjects of this research are students majoring in chemistry at Universitas Negeri Surabaya, Indonesia. StudentsÃ¢â‚¬â„¢ conception status is determined by the result of a conception test equipped with the Certainty of Response Index. With descriptive analysis techniques, results indicated that students who had the potential misconceptions status at the beginning had experienced self-actualization: (1) the number of students who have Ã¢â‚¬Å“the right conceptÃ¢â‚¬Â is more than those who Ã¢â‚¬Å“do not know the conceptÃ¢â‚¬Â and have Ã¢â‚¬Å“misconceptions,Ã¢â‚¬Â and (2) the number of students who have status least misconception. Based on the results of the study, the implementation of metacognitive skills-based teaching materials can overcome student misconceptions in energetic material.